Correlation Between Empathy and Social Acceptance of Non-Disabled Students Towards Students with Special Needs in Inclusive Schools - Anjarwati, Ajeng Lovi; Yusuf, Munawir; Supratiwi, Mahardika (Department of Special Education, 2024)
This study aims to find out the relationship between empathy and social acceptance Non-Special Needs Students for Special Needs Students at SMPN 14 Inclusive School Madiun. This study uses a quantitative approach with a type of correlational research. The subjects in this study are non-special needs students in grades VIII B and VIII C at SMPN 14 Madiun as many as 46 people. The data collection technique in this study uses the Empathy (α= 0.896) and Social Acceptance Scale (α=0.912). Data analysis techniques in research using simple linear regression. The regression test showed a correlation value of 0.862 with F count = 126.793 and sig 0.000. The result of the determination coefficient is 0.742, the value showed that the contribution of empathy to social acceptance was 74.2%, the rest was 25.8% influenced by other variables. Based on the results of the study, it can be concluded that there is a relationship between significant between empathy and social acceptance of non-special needs students to students with special needs at SMPN 14 Madiun inclusive school